Impact of COVID‐19 on wound care in Germany. Issue 4 (7th February 2021) - Schlager, Justin Gabriel; Kendziora, Benjamin; Patzak, Leilah; Kupf, Sophie; Rothenberger, Christoph; Fiocco, Zeno; French, Lars E.; Reinholz, Markus; Hartmann, Daniela
Abstract: Recent studies showed that the COVID‐19 pandemic caused collateral damage in health care in terms of reduced hospital submissions or postponed treatment of other acute or chronic ill patients. An anonymous survey was sent out by mail to patients with chronic wounds in order to evaluate the impact of the pandemic on wound care. Sixty‐three patients returned the survey. In 14%, diagnostic workup or hospitalisation was cancelled or postponed. Thirty‐six percent could not seek consultation by their primary care physician as usual. The use of public transport or long travel time was not related to limited access to medical service ( P  = .583). In ambulatory care, there was neither a significant difference in the frequency of changing wound dressings ( P  = .67), nor in the person, who performed wound care ( P  = .39). There were no significant changes in wound‐specific quality of life ( P  = .505). No patient used telemedicine in order to avoid face‐to‐face contact or anticipate to pandemic‐related restrictions. The COVID‐19 pandemic impaired access to clinical management of chronic wounds in Germany. It had no significant impact on ambulatory care or wound‐related quality of life. Telemedicine still plays a negligible role in wound care.